2009
DOI: 10.2478/s11686-009-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of arthropod-borne hematozoans in wild mammals from Brazil, Venezuela and Spain

Abstract: A survey of Babesia, Theileria and Hepatozoon was conducted in wild mammals, including the capybara (Hydrochaeris hydrochaeris; n = 14) from Brazil, the jaguar (Panthera onca; n = 2) and crab-eating raccoon (Procyon cancrivorus; n = 4) from Venezuela, and the red deer (Cervus elaphus; n = 70), red squirrel (Sciurus vulgaris; n = 5) and Eurasian pine marten (Martes martes; n = 3) from Spain. Diagnostic procedures included both microscopy and molecular methods (PCR and sequencing of the 18S rRNA gene). Microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 49 publications
1
22
0
9
Order By: Relevance
“…As in the present study, no free-ranging jaguars in Venezuela, French Guiana and the Pantanal were found to be positive for Babesia spp. (Criado-Fornelio et al, 2009;Thoisy et al, 2000). André et al (2011) reported captive jaguars seropositive for B. vogeli, however, the same individuals were negative when performing molecular testing.…”
Section: Discussionmentioning
confidence: 99%
“…As in the present study, no free-ranging jaguars in Venezuela, French Guiana and the Pantanal were found to be positive for Babesia spp. (Criado-Fornelio et al, 2009;Thoisy et al, 2000). André et al (2011) reported captive jaguars seropositive for B. vogeli, however, the same individuals were negative when performing molecular testing.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences have been submitted to GenBank (accession numbers KF939620 to KF939628) and were subjected to the basic local alignment search tool (BLAST) sequence similarity search to identify the most similar available sequences. Forty-seven named or unnamed Hepatozoon sequences were retrieved from GenBank (Carreno et al 1999;Oyamada et al 2005;Criado-Fornelio et al 2006;Sloboda et al 2007;Kubo et al 2008;Criado-Fornelio, Buling, Casado et al 2009;Criado-Fornelio, Buling, Pingret et al 2009;Merino et al 2009;Maia et al 2011Maia et al , 2012Barta et al 2012) and were aligned with the derived sequences using ClustalW software implemented in BioEdit (Hall 1999). Phylogenetic relationships were estimated using maximum likelihood (ML) and Bayesian analyses.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Amostras de paca (C. paca) do Pará foram positivas e as sequências obtidas apresentaram similaridade (95%) com Babesia sp., descrita recentemente em capivaras (Hydrochaeris hydrochaeris) do Rio Grande do Sul (CRIADO-FORNELIO et al, 2009). Uma das amostras de C. paca também foi positiva para o gênero Hepatozoon, sendo a sequência similar (95%) a Hepatozoon felis.…”
Section: Infecção Por Rickettsia Em Carrapatosunclassified
“…Uma das amostras de C. paca também foi positiva para o gênero Hepatozoon, sendo a sequência similar (95%) a Hepatozoon felis. No Brasil, foi relatada a infecção por Hepatozoon canis em capivaras (H. hydrochaeris) no Rio Grande do Sul (CRIADO-FORNELIO et al, 2009), contudo não há relatos da infecção por H. felis em C. paca, sendo este o primeiro.…”
Section: Infecção Por Rickettsia Em Carrapatosunclassified